1989
DOI: 10.1111/j.1600-0447.1989.tb08583.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of mental health services in south Verona and Groningen

Abstract: A comparison was made of the utilization of mental health services in a psychiatric case register area in Italy (south Verona) and one in the Netherlands (Groningen). All residents living in these areas who contacted a mental health service in 1982 were traced and followed for a period of one year. The year prevalence rates differed considerably (110/10,000 in south Verona and 329/10,000 in Groningen). Rates of single consulters were similar in both areas, while those of chronic inpatients were more than 11 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
6

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 17 publications
0
11
0
6
Order By: Relevance
“…In a review of studies on the patterns of care in generic mental health services Hansson & Sandlund (1992) found that a small proportion of service users use a large proportion of resources. Lavik (1983) found an 'inequality' of service use, with 10% of service users using 75% of service resources, and Sytema et al (1989) found that 8% of service users were using 60% of the services. This review also highlighted a number of factors that could be used to predict heavier service use, such as living alone or having no occupation.…”
Section: Introductionmentioning
confidence: 99%
“…In a review of studies on the patterns of care in generic mental health services Hansson & Sandlund (1992) found that a small proportion of service users use a large proportion of resources. Lavik (1983) found an 'inequality' of service use, with 10% of service users using 75% of service resources, and Sytema et al (1989) found that 8% of service users were using 60% of the services. This review also highlighted a number of factors that could be used to predict heavier service use, such as living alone or having no occupation.…”
Section: Introductionmentioning
confidence: 99%
“…Lo studio dei pattern di utilizzazione dei servizi psichiatrici da parte dei pazienti residenti in un territorio definito e stato oggetto di indagini approfondite negli ultimi anni (Tansella, 1987;Tansella et al, 1994;Sytema et al, 1989a;Balestrieri et al, 1987;1989;Viscogliosi-Calabrese et al, 1990). I patterns di utilizzazione sono stati descritti utilizzando indici epidemiologici di tipo temporale, di tipo quantitativo e di tipo combinato.…”
Section: Discussioneunclassified
“…Nel lavoro originario di Lavik (1983) -che ha introdotto questo tipo di misura -il punteggio-soglia era determinato in modo arbitrario e corrispondeva a 200 punti in due anni; in altri lavori il punteggio-soglia e stato calcolato con l'analisi della varianza, cosi che tale punteggio -non piii scelto arbitrariamente -risultava dipendente dalle caratteristiche della coorte esaminata (Tansella etal., 1986;Sytema et al, 1989a). Se nel caso dei lungoassistiti vi e, allo stato attuale delle cose, pressocche completo accordo nella letteratura sui criteri di definizione, per cio che riguarda gli alti utilizzatori, ferma restando la attribuzione di determinati punteggi ai diversi tipi di contatto (ricovero, day-hospital, territorio), sono stati adottati due criteri diversi per individuare il punteggio soglia per definire gli alti utilizzatori.…”
Section: Discussioneunclassified
“…It developed during the dawn of the deinstitutionalization era in the 1960s and has been rapidly expanding during the last decade. Outcome measures have been predominantly used to evaluate the effects of major changes in the health care system (Wing, 1972;Nielsen et al, 1981;Hafner et al, 1980;Tansella et al, 1991) and to compare the outcomes of different mental health care systems (Sytema, 1994;Sytema et al, 1989) and programs (Test et al, 1978). Unfortunately, the results of mental health service research have rarely made a major impact on the political arid administrative level of planning and development of mental health services.…”
Section: Helle Charlotte Knudsenmentioning
confidence: 99%